Efficient modelling of IEEE 802.11p MAC output process for V2X interworking enhancement. Issue 4 (1st July 2018) - Salem, Fatma; Elhillali, Yassin; Niar, Smail
Abstract : Vehicle‐to‐anything (V2X) is a promising communication technology, which expected to revolutionise the ground transportation system by improving traffic safety and efficiency for people on roads. The future deployment of V2X requires interworking between different access technologies, i.e. dedicated short‐range communications (DSRCs) and cellular networks. However, to achieve an efficient V2X interworking, the authors need to resolve the multi‐hop issue, mainly originating from the V2X hybrid architecture. To resolve this issue and consequently to enhance the interconnected system, characterising the output process of IEEE 802.11p‐based DSRC medium access control protocol is of a fundamental importance. This study proposes regenerative model to provide a complete description of IEEE 802.11p output process. The accuracy of the model is verified through extensive simulations. As a case study, the proposed model is compared with Poisson model in the performance evaluation of V2X interworking. Numerical and simulation results verify the ability of the regenerative model to capture the deviations of the actual output process of IEEE 802.11p under different traffic intensities as compared with the Poisson model.